2019
DOI: 10.4103/ajts.ajts_125_17
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of donor direct antiglobulin test positivity: Implications in cross-matching and lessons learnt

Abstract: Direct Antiglobulin Test is a method of demonstrating the presence of antibody/ complement bound to red cell membrane by using AHG to form a visible agglutination reaction. DAT positivity is seen in immune mediated haemolytic anaemias, however rarely non immune mediate haemolytic anaemias also show DAT positivity. DAT positivity predictive of 83% of autoimmune haemolytic anaemia and 1.4% cases without haemolytic anaemia. Screening of blood donors for DAT is usually not recommended traditionally by any guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…These can miss DATpositive donor units unless DAT screening of donors is included in pre-transfusion testing. Similar cases of incompatible crossmatch due to DAT-positive donors were reported by Puri et al and Vidushi et al [6,8]. However, DAT positivity has been reported in 0.008% of donors [9].…”
Section: Discussionsupporting
confidence: 68%
“…These can miss DATpositive donor units unless DAT screening of donors is included in pre-transfusion testing. Similar cases of incompatible crossmatch due to DAT-positive donors were reported by Puri et al and Vidushi et al [6,8]. However, DAT positivity has been reported in 0.008% of donors [9].…”
Section: Discussionsupporting
confidence: 68%
“…[ 9 ] Antibody in the majority of such donors, including that in the present study, showed the immunoglobulin subclass as IgG1 which is otherwise known to cause clinical hemolysis, yet remained innocuous for unknown reasons. Many times, such healthy donors with positive DAT are noticed during crossmatch tests in the antiglobulin phase[ 1 10 ] as was the case with our donor.…”
Section: Discussionmentioning
confidence: 84%
“…There are no data on adverse consequences of transfusion of DAT‐positive blood. Institutions that use only saline phase cross‐match or computerized cross‐match cannot detect DAT‐positive units in this way, so it happens that such units are used in patients [11]. Based on literature data, IgG‐coated erythrocytes are not expected to have reduced survival after transfusion [12].…”
Section: Discussionmentioning
confidence: 99%